Evaluation of QRIS-Based Payment Gateway Implementation in order to Encourage Revenue Growth at MSMEs in the Tourism Business Sector in Semarang City - Eva Purnamasari (Cita konsultindo, 2023)
The Central Bureau of Statistics (2022), released data that the contribution to tourism gross domestic income (GDP) in 2022 until the third quarter reached 3.6%, this figure shows a significant increase from 2021 at 2.4%. Semarang is one of the tourist destination cities in Indonesia that is relatively fast in terms of tourism revitalization. The government continues to encourage digitalization in existing tourist destinations, where one of the most obvious is digitalization in terms of payment. The government through Bank Indonesia is now promoting its digital product, QRIS, which is predicted to boost the digital economy. However, MSMEs in the tourism sector in Semarang City are still partially shifting to QRIS-based payment gateways. The results of this study indicate that the use of the QRIS Payment System has a positive and significant effect on the growth of MSME revenue in the tourism business sector in Semarang City. This can be translated that the implementation of the QRIS-based Payment Gateway has a positive impact on the revenue growth of MSMEs in the Tourism Business Sector in Semarang City. Then based on the statements of respondents of MSMEs in the Tourism Business Sector in Semarang City who use QRIS, there are several obstacles that are felt, namely: There are still those who do not understand how to use QRIS, constrained by the network, the slow process of disbursing funds in real time / instant, the cost of using QRIS charged to merchants (traders). However, these obstacles are considered not to have too much impact on their overall business income.